Prevalence of thyroid dysfunction in type 2 diabetes mellitus: a case control study - Telwani, Ajaz Ahmad; Wani, Zahid Hussain; Ashraf, Younis; Shah, Aejaz Ahmad (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes mellitus and thyroid disorders are the most common endocrine disorders worldwide. Various studies have found that diabetes and thyroid disorders mutually influence each other and both disorders tend to coexist. So, we conducted a study to find out the prevalence of thyroid disorders in patients of type 2 diabetes mellitus. Methods: This study was conducted on 100 diabetic patients and 100 controls. All the participants were evaluated for thyroid dysfunctions by testing thyroid profile. The correlation of prevalence of thyroid disorder with age distribution, gender distribution, BMI, duration of diabetes and HbA1C was then done. Results: The prevalence of thyroid dysfunctions were high in diabetic patients compared to controls (29% versus 9%, P value <0.001). Most common thyroid disorder in diabetic patients was subclinical hypothyroidism (16%) while least common was hyperthyroidism (1%). The levels of serum T3 and T4 were significantly low while serum TSH levels were significantly high in diabetic group compared to control group. Prevalence of thyroid disorders in diabetics were significantly more in patients with age ≥ 50 years, more in females, more in patients with BMI ≥ 30 and more in patients with duration of diabetes ≥ 5 years. The association of prevalence of thyroid disorders with HBA1C was not significant. Conclusions:Current study showed high prevalence of thyroid dysfunctions in diabetic patients. We conclude that screening for thyroid dysfunction among patients with diabetes mellitus should be routinely performed, so as to recognize these dysfunctions early.